Penggunaan Analisis Kontekstual atau Analisis Konteks Sastra untuk Membangun Doktrin Teologi dalam Surat Galatia - Andrew Lucas Tjong; Sri Binar; Priskila Elizabeth Rawung (Sekolah Tinggi Teologi Bethel Ambon, 2023)
This research focuses on a contextual analysis to develop doctrine within the Epistle to the Galatians as a hermeneutical study. Contextual analysis is employed in order to uncover the theological content found in Galatians and to structure it according to coherent lines of thought. The study applies hermeneutics to the Epistle to the Galatians using contextual analysis, including both the immediate and broader context, to identify the interrelated connections within the text that form the integrity of the letter, thereby allowing theological doctrines to be drawn. Based on the method used, five doctrines are identified: Proper, Christology, Pneumatology, Soteriology, and Ecclesiology. Christology holds the most prominent place in Galatians, primarily because the central issue addressed in the letter concerns “a different gospel” (Gal. 1:6–7).